Modelling the impact of Magnetohydrodynamics (MHD) nanofluid flow on cooling of engineering systems - Tshivhi, Khodani Sherrif (Stellenbosch : Stellenbosch University, 2021)
Thesis (MMil)--Stellenbosch University, 2021.